Paw patrol. Rescue knights [videorecording (DVD)] (Nickelodeon, 2022)
The PAW Patrol Rescue Knights must protect Barkingburg from Claw, a mischievous pup, and his dragon! No rescue is too big, and no pup knight is too small! With new knightly vehicles and armor, the pups take to land, air, and moat to save the kingdom!